Optimal Equi-Partition of Rectangular Domains for Parallel Computation - Meyer, Robert R.; Christou, Ioannis T. (My University, 1995)
We present an efficient method for the partitioning of rectangular domains into equi-area sub domains of minimum total perimeter. For a variety of applications in parallel computation, this corresponds to a load-balanced distribution of tasks that minimize interprocessor communication. Our method is based on utilizing, to the maximum extent possible, a set of optimal shapes for sub domains. We prove that for a large class of these problems, we can construct solutions whose relative distance from a computable lower bound converges to zero as the problem size tends to infinity. PERIX GA, a genetic algorithm employing this approach, has successfully solved to optimality million variable instances of the perimeter minimization problem and for a one billion variable problem has generated a solution within 0.32% of the lower bound. We report on the results of an implementation on a CM5 supercomputer and make comparisons with other existing codes.
Keywords: parallel computation